2017
DOI: 10.1080/09540121.2017.1384534
|View full text |Cite
|
Sign up to set email alerts
|

An educational initiative in response to identified PrEP prescribing needs among PCPs in the Southern U.S.

Abstract: Pre-exposure prophylaxis (PrEP) is an effective HIV prevention method, but many primary care physicians (PCPs) have not incorporated PrEP into practice. While PrEP may be a key strategy to reducing high HIV transmission rates in the southern US, knowledge about PrEP prescribing patterns among PCPs in this region is lacking. An online survey was sent to a large network of PCPs at an academic medical center in North Carolina in October 2015. The survey was repeated in September 2016, after an educational interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 9 publications
4
48
0
Order By: Relevance
“…Of the 28 articles included in our systematic review, 18 studies reported lack of provider knowledge as a barrier to PrEP prescription. 24,[26][27][28]31,32,34,38,[40][41][42][43][44][45][46][47]49 PrEP awareness among PCPs increased steadily, from 24% to 66% between 2009 and 2015. 44 However, PrEP knowledge remained low, with only 17% of providers indicating that they had read the CDC guidelines in 2014.…”
Section: Lack Of Knowledgementioning
confidence: 99%
See 4 more Smart Citations
“…Of the 28 articles included in our systematic review, 18 studies reported lack of provider knowledge as a barrier to PrEP prescription. 24,[26][27][28]31,32,34,38,[40][41][42][43][44][45][46][47]49 PrEP awareness among PCPs increased steadily, from 24% to 66% between 2009 and 2015. 44 However, PrEP knowledge remained low, with only 17% of providers indicating that they had read the CDC guidelines in 2014.…”
Section: Lack Of Knowledgementioning
confidence: 99%
“…49 Similarly among both PCPs in North Carolina and family planning providers throughout the United States, the most frequently reported barrier to prescribing PrEP was a lack of knowledge. 32,43 Seventy-five percent of the family planning providers and 42% of the PCPs reported they were uncomfortable prescribing PrEP due to a lack of knowledge. Notably, a majority of both PCPs and family planning providers stated that they would be willing to provide PrEP with more training.…”
Section: Lack Of Knowledgementioning
confidence: 99%
See 3 more Smart Citations